PENGARUH BUDAYA ORGANISASI, KEMAMPUAN KERJA DAN FASILITAS KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PLTA KERINCI MERANGIN HYDRO - Jufitra, Jeke; Saputra, Atrio; Sudirman, Sudirman; Liantifa, Melifia (Jurnal Ekonomi Sakti, 2024)
This study aims to determine: 1) Is there an influence of Organizational Culture on the work effectiveness of the employees of the Kerinci Merangin Hydro Hydroelectric Power Plant, how much is the effect partially? ?, 3) Is there any influence of Work Facilities on the work effectiveness of the employees of the Kerinci Merangin Hydro Hydro Power Plant and how much of the effect is partially? big effect simultaneously? The research methodology used is descriptive qualitative and descriptive quantitative approaches. The research results are; 1) partially, there is an influence of Organizational Culture on the work effectiveness of the employees of the Kerinci Merangin Hydro Hydroelectric Power Plant, 2) partially, there is an influence between the work ability of the employees of the Kerinci Merangin Hydro Hydroelectric Power Plant, 3). Partially, there is no influence of facilities on the work effectiveness of the employees of the Kerinci Merangin Hydro Hydro Power Plant, 4) Simultaneously, there is the influence of organizational culture, ability and work facilities simultaneously on the work effectiveness of the employees of the Kerinci Merangin Hydro Hydro Power Plant.